SCALE: Automatically Finding RFC Compliance Bugs in DNS Nameservers - Kakarla, Siva Kesava Reddy; Beckett, Ryan; Millstein, Todd; Varghese, George (NSDI 2022, 2022)
The Domain Name System (DNS) has intricate features that interact in subtle ways. Bugs in DNS implementations while handling combinations of these features can lead to incorrect or implementation-dependent behavior, security vulnerabilities, and more. We introduce the first approach for finding RFC compliance errors in DNS nameserver implementations via automatic test generation. Our SCALE (Small-scope Constraint-driven Automated Logical Execution) approach jointly generates zone files and corresponding queries to cover RFC behaviors specified by an executable model of DNS resolution. We have built a tool called Ferret based on this approach and applied it to test 8 open-source DNS implementations, including popular implementations such as Bind, PowerDNS, Knot, and Nsd. Ferret generated over 13K test files, of which 62% resulted in some difference among implementations. We identified and reported 30 new unique bugs from these failed test cases, including at least one bug in every implementation, of which 20 have already been fixed. Many of these existed in even the most popular DNS implementations, including a new critical vulnerability in Bind that attackers could easily exploit to crash DNS resolvers and nameservers remotely.